"We're checking them out": Indigenous and non-Indigenous research participants' accounts of deciding to be involved in research. Issue 1 (December 2016) - Guillemin, Marilys; Gillam, Lynn; Barnard, Emma; Stewart, Paul; Walker, Hannah; Rosenthal, Doreen
Abstract Background It is important for researchers to understand the motivations and decision-making processes of participants who take part in their research. This enables robust informed consent and promotes research that meets the needs and expectations of the community. It is particularly vital when working with Indigenous communities, where there is a history of exploitative research practices. In this paper, we examine the accounts of Australian Indigenous and non-Indigenous research participants in terms of how and why they agree to take part in research. Methods A qualitative research approach was employed to undertake individual interviews with 36 research participants in Victoria, Australia. Eight participants identified as Indigenous and 28 were non-Indigenous. Thematic analysis was used to interpret the data. Results There were stark differences between Indigenous and non-Indigenous research participants in terms of why and how they decided to participate in research. For Indigenous participants, taking part in research was primarily to benefit their communities rather than for personal interests. Indigenous participants often started from a position of caution, and showed a considered and deliberate process of decision making. In weighing up their decision to participate, some Indigenous participants clearly articulated what was valued in conducting research with Indigenous communities, for example, honesty, reciprocity, and respect; these values were explicitly used to assist their decision whether or not to participate. This was in contrast to non-Indigenous participants who took researchers' claims on face value, and for whom deciding to participate in research was relatively straightforward. The motivations to participate of non-Indigenous participants were due to personal interests, a desire to help others, or trust in the medical practitioner who recruited them for the research project. Conclusion Understanding research participants' motivations about taking part in research is important. This is particularly relevant for Indigenous communities where there is a reported history of research abuse leading to mistrust. This understanding can lead to research practice that is more respectful and responsive to the needs of Indigenous communities and abides by the values of Indigenous communities. Moreover it can lead to more ethical and respectful research practice for all.